2016
DOI: 10.1038/ncomms10871
|View full text |Cite
|
Sign up to set email alerts
|

Stabilin-2 modulates the efficiency of myoblast fusion during myogenic differentiation and muscle regeneration

Abstract: Myoblast fusion is essential for the formation of skeletal muscle myofibres. Studies have shown that phosphatidylserine is necessary for myoblast fusion, but the underlying mechanism is not known. Here we show that the phosphatidylserine receptor stabilin-2 acts as a membrane protein for myoblast fusion during myogenic differentiation and muscle regeneration. Stabilin-2 expression is induced during myogenic differentiation, and is regulated by calcineurin/NFAT signalling in myoblasts. Forced expression of stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
113
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 58 publications
7
113
2
Order By: Relevance
“…At the same time, expressions of the satellite cell marker paired box protein 7 (PAX7; Zhang et al , ; Bi et al , ) and the satellite cell activation marker myoblast determination protein (MyoD; Zhang et al , ; Bi et al , ) were not different between the mGPDH −/− and WT mice (), which suggests that mGPDH has no significant effects on myoblast quantity and activation. However, the differentiation markers myogenin and myh3 (Park et al , ) were reduced in the mGPDH −/− mice (Fig J and K), which is consistent with our in vitro data and indicates that mGPDH deletion inhibits skeletal muscle regeneration by diminishing myoblast differentiation.…”
Section: Resultssupporting
confidence: 91%
“…At the same time, expressions of the satellite cell marker paired box protein 7 (PAX7; Zhang et al , ; Bi et al , ) and the satellite cell activation marker myoblast determination protein (MyoD; Zhang et al , ; Bi et al , ) were not different between the mGPDH −/− and WT mice (), which suggests that mGPDH has no significant effects on myoblast quantity and activation. However, the differentiation markers myogenin and myh3 (Park et al , ) were reduced in the mGPDH −/− mice (Fig J and K), which is consistent with our in vitro data and indicates that mGPDH deletion inhibits skeletal muscle regeneration by diminishing myoblast differentiation.…”
Section: Resultssupporting
confidence: 91%
“…When examining the phosphorylation status of nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) as a marker of calcineurin signaling, compared with WT we found that NFATc1 phosphorylation relative to total NFATc1 was significantly lower in Pln OE but not Pln OE / Sln KO soleus (Fig 5A). Calcineurin-mediated activation of NFATc1 increases the expression of stabilin-2; a phosphatidylserine receptor required for myoblast fusion [40]. Corresponding well with the significant dephosphorylation of NFATc1 only in the Pln OE mice, we found a significant elevation in stabilin-2 expression only in Pln OE soleus compared with WT (Fig 5B).…”
Section: Resultssupporting
confidence: 76%
“…Contrasting the prevailing view that PS exposure during cell-cell fusion is a consequence of apoptosis and caspase activation [17][18][19] , our experiments clearly demonstrate that apoptosis is not required for CaPLSase-mediated cell-cell fusion. Application of Q-VD, a pan-caspase inhibitor, has no effects on trophoblast fusion ( Figure 1D and 1E), suggesting that apoptosis and caspase-activated lipid scramblases play a dispensable role in PS exposure during trophoblast fusion.…”
Section: Discussioncontrasting
confidence: 99%
“…types. The notion of PS exposure as an early hallmark of apoptosis led to the prevailing view of PS exposure during cell-cell fusion: apoptosis is responsible for PS exposure-mediated cell-cell fusion [17][18][19] .…”
mentioning
confidence: 99%